(untitled) (Revista Electrónica REDINE, 2021)
The scientific journal “CALIDAD, TECNOLOGÍA Y DESARROLLO AGROINDUSTRIAL (CATEDEA)” (ISSN: 2477-9288), was created in 2015, by a group of teachers from the Agroindustrial program, with the purpose of creating a journal specialized in Agro and Marine Sciences, having as headquarters the Nucleus Dr. Argimiro Bracamonte located in the Morán municipality specifically in the town of Tocuyo, Lara state (Venezuela). It is an open access scientific journal of the Dean of Agronomy of the Universidad Centroccidental Lisandro Alvarado (UCLA), indexed and refereed, published annually and in the Spanish language. Its editorial line includes specialized topics in agribusiness, also allowing the development of strategies for quality assurance in food production, guaranteeing quality, safety and food safety.